Desenvolvimento de um equipamento recolhedor de resíduos de colheita da soja - Schöffel, Rubem (2014)
In most soybean producing regions in Brazil, harvesting season of this crop coincides with a period of shortages of dry matter for feeding ruminants, affecting meat and milk production. The soybean harvest residues present nutritional composition able to supply part of the food demands of these herds, however, in this operation, machines thrashing and storing grains and discard the other parts (residues). To facilitate the use of these residues, one challenge is to mechanize its gathering after harvesting crops. The aim of this work was to design, build and test a device to collect soybean harvest residues from the cleaning mechanism of the harvester. The equipment consists of baffle plates, a screw conveyor arranged transversely to the harvester and a centrifugal fan installed on the side. To quantify the pods husks, whole plants were uprooted and broken down into pods husks, stems and grains. The relation between pods husks and grains was of 0,43 in 2012 and 0,34 in 2013. The pods husks from the cleaning mechanism of the harvester were collected, using the equipment developed, and weighed and the relation between the pods husks and grains was of 0,33 in 2012. Using a plot harvester the total residues were collected and the relation between pods husks and grain in 2012 was 0,48 and 0,57 for cv. Apolo and Syn 1157, respectively. And, the pods husks collected were qualified by bromatological analysis and the contents based on the dry matter to crude protein, neutral and acid detergent fiber, were 5,9, 79,7 and 59,3%, respectively. It was conducted an experiment to evaluate the effect of replacement of ryegrass hay for soybean pods husks on the diet of ewe lambs, it was observed the increase in the ratio of pods husks on the diet improved animal gain weight performance.